Assessment of climate change in different regions of Karnataka state (MAUSAM, 2024)
At the regional level, climate change has significant influences on crop productivity and food security. A climate change study was carried out using different parametric indices like rainfall attributes, temperature, and humidity from 58 years of climatic data (1964-2017) in Karnataka. The climatic period was divided into the Pre-climate change period- P1 (1964-1990) and the climate change period- P2 (1991-2017) with 27 years. The result shows annual rainfall and rainy days were increased in South Interior Karnataka (SIK) and Malnad regions and reduced in North Interior Karnataka (NIK) and Coastal regions. Dakshina Kannada, Yadgir, Kalabarugi, Udupi and Kodagu districts showed a significant reduction in receiving rainfall and an increase in Shivamogga, Hassan, Kolar and Chitradurga districts from the P1 to P2 period. NIK and SIK regions are highly prone to drought vulnerability compared to Malnad and Coastal regions. The occurrence of droughts wasincreasing,the temperature trend is increased and the relative humidity trend is decreasing in the P2 period. Assessment of climate variability in P1 and P2 helps to adopt preciseuse of water, nutrient and different crop-specific management in different zones of Karnataka.